Des vestiges liés à la phase de construction de l’aqueduc de la Brévenne à Limonest (Métropole de Lyon) ? - Stéphane Ardouin; Cécile André-Chaze (Gallia)
Following an archaeological diagnosis made in 2009 under the responsibility of J. Grasso for the National Institute for Preventive Archaeology (INRAP), an excavation was carried out in May 2014 by the Lyon Archaeology Service (SAVL) on a section of the Brevenne aqueduct at Limonest, located on a ridge line between two valleys. Two straight ditches were revealed, running perpendicular to the trunk of the aqueduct pipe and on both sides of a slight bend formed by the pipeline.Observed over a distance of 16 m (in the case of the longest ditch), but probably longer in all, these ditches have a U-shaped profile with a flat bottom and vertical sides, measuring approximately 37 cm in width. Both widen as they approach the pipeline and dip slightly towards the slope. Their similar fillings contained many fragments of architectural terracota. An imbrex, two fragments of which came from both ditches, is evidence of the contemporaneity of the fillings. These can be compared with other ditches discovered upstream on the route of the aqueduct, in the neighbouring plot, at Limonest during a dig led by M. Monin for SAVL in 2010-2011, at Lentilly during a dig led by C. Coquide for INRAP in 2014, and at Dardilly during a rescue archaeology dig led by B. Rostaing-Taillard, R. Saby and D. Gerboud for AFAN (now INRAP) in 1991.All these ditches share common features. The ditches found at Limonest in 2014 and in the neighbouring plot in 2010-2011 have parallel trajectories. If we had a hypothetical ditch discovered in this same excavation, the four ditches would be evenly spaced between 15 and 20 m apart. At Dardilly and Lentilly, the fillings are close and in the latter case, the width in contact with the aqueduct is the same as that observed at Limonest. At Dardilly and Lentilly, the ditches are intersected by the pipeline’s installation trench. The dating of ceramics and of a complete tegula discovered at Limonest corroborates the likelihood that they were dug prior to or contemporary with the construction of the aqueduct.The similarity of these ditches, their repetition at regular intervals and their location on several sections of the aqueduct route suggest a global strategy relating to the construction of the aqueduct rather than to occasional repairs. The absence of similar ditches on Lyon’s three other aqueducts and, to our knowledge, on any other aqueduct, prevents us from reaching a robust conclusion. In the current state of our excavations and knowledge, we suggest that they should be identified as standardised structures or storage areas or as drains for evacuating rainwater during the construction of the aqueduct in somewhat clayey soils.